Synthesis, Modification and Prospect of Bio-based Polyurethane - Kangjia SONG; Feifei ZHANG; Jie LIU; Liqiang JIN; Deyi ZHU (Pige Kexue Yu Gongcheng, 2025)
Bio-based polyurethane is a type of polyurethane material primarily derived from natural bio-based raw materials, synthesized through the reaction of bio-based polyols and bio-based isocyanates. This material has garnered attention due to its natural origin, renewability, and favorable biocompatibility and biodegradability, making it suitable for applications in medical, food packaging, and consumer goods sectors. This review covered the key raw materials (bio-based polyols and isocyanates), preparation methods, and functional modifications of bio-based polyurethanes. Among these, stimuli-responsive bio-based polyurethanes show great potential for future research. Through this review, we aim to provide viable directions for the future development of bio-based polyurethane.